2018
DOI: 10.1080/02699931.2018.1496068
|View full text |Cite
|
Sign up to set email alerts
|

Negativity bias in false memory: moderation by neuroticism after a delay

Abstract: The negativity bias is the tendency for individuals to give greater weight, and often exhibit more rapid and extreme responses, to negative than positive information. Using the Deese-Roediger-McDermott illusory memory paradigm, the current study sought to examine how the negativity bias might affect both correct recognition for negative and positive words and false recognition for associated critical lures, as well as how trait neuroticism might moderate these effects. In two experiments, participants studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…Next, a high number of the negative NAPS (N = 51) images were located in the "false alarm" cluster, compared to GAPED (N = 28), and IAPS database (N = 10). This datum also replicated the findings according to which negative stimuli results more frequently induced false memories than neutral and positive stimuli (Brainerd et al, 2008;Norris et al, 2019), and consequently resulted in higher rates of false alarms (Bisby and Burgess, 2014). Hypothetically, negative stimuli were encoded with gist compared to verbatim representations.…”
Section: Discussionsupporting
confidence: 84%
“…Next, a high number of the negative NAPS (N = 51) images were located in the "false alarm" cluster, compared to GAPED (N = 28), and IAPS database (N = 10). This datum also replicated the findings according to which negative stimuli results more frequently induced false memories than neutral and positive stimuli (Brainerd et al, 2008;Norris et al, 2019), and consequently resulted in higher rates of false alarms (Bisby and Burgess, 2014). Hypothetically, negative stimuli were encoded with gist compared to verbatim representations.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, there is extensive evidence suggesting that trait differences in personality are associated with variability in behavioral and neural responses to emotion 34,35 . For example, it is well-established that neuroticism explains variability in negativity bias [36][37][38][39] and is related to mood and anxiety symptoms in both clinical 40 and nonclinical samples 41 . And emerging research provides some evidence to suggest that valence bias per se is related to trait-like differences, including trait anxiety 42 .…”
Section: Social Connectedness and Negative Affect Uniquely Explain Inmentioning
confidence: 99%
“…Second, if professional morality was crucial, drawing support from past relevant findings (Kroneisen & Bell, 2013; Norris et al, 2019; Rozin et al, 2010; Rozin & Royzman, 2001), remarkable negativity bias would be expected in both item memory and source memory, which was irrespective of whether the source type was the doctor or the lawyer.…”
Section: Methodsmentioning
confidence: 73%
“…To this day, a large number of past studies have confirmed that compared with positive (or good) information, negative (or bad) information tends to have more affect on memory. It resulted in a phenomenon termed as negativity bias , which showed better performance for negative (or bad) versus positive (or good) information (Kroneisen & Bell, 2013; Norris, Leaf, & Fenn, 2019; Rozin et al, 2010; Rozin & Royzman, 2001). One credible explanation for the negativity bias is that negative (or bad) (e.g., cheating, disgusting, egoistic) entities are more contagious versus positive (or good) (e.g., cooperative, adorable, altruistic) ones, thus leading the former ones to hold greater strength, dominance, as well as more complexity in the course of memory, causing more cognitive resources (including attention) to be assigned to negative (or bad) things than to positive (or good) things (Kroneisen & Bell, 2013; Norris et al, 2019; Rozin et al, 2010; Rozin & Royzman, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation